Morphological controls on delta‐canyon‐fan systems: Insights from stratigraphic forward models. Issue 2 (11th October 2021) - Wan, Li; Bianchi, Valeria; Hurter, Suzanne; Salles, Tristan; Zhang, Zhijie; Yuan, Xuanjun
Abstract: Morphology is one of the principal driving forces governing the sedimentology and evolution of delta‐canyon‐fan systems. However, quantified and systematic studies of morphological controls are still very limited. This study applied hydraulic‐based stratigraphic forward modelling to investigate the impacts of morphological parameters on sediment budget partitioning and channel network of delta‐canyon‐fan systems on passive margins. A total of six sets of stratigraphic forward models are built using 47 initial bathymetries with six varying morphological parameters: shelf gradient; shelf width; slope gradient; canyon sinuosity; canyon depth; and basin gradient. The quantified relationships between morphological parameters and sedimentological parameters (dimensions, deposition/erosion volume/area, number of tributaries and slope channels) are investigated. The causes behind the relationships are explored by analyzing the response of qualified sedimentary features to morphological controls, such as grain‐size distribution, channel migration and sequence stratigraphic frame. The results suggest that low shelf gradient, low shelf width, high canyon gradient and low canyon sinuosity are beneficial for sediment budget partitioning into deep basins and turbidity currents to flow inside canyons. Low canyon depth also promotes sediment delivery but results in more channels on canyon flanks. For the delta, channel lateral migration increases then decreases with increasing shelf gradient due to the gradient threshold in determining channel sinuosity; delta size increases then stops increasing with increasing shelf width due to the shelf width threshold in determining the balance between accommodation and sediment supply. For the canyon, low canyon gradient, high canyon sinuosity and low canyon depth have similar effects on canyons, all resulting in significant channel translation and canyon widening but less canyon head retrogradation. This study improves the knowledge of controlling factors and sediment transport regime of a delta–canyon–fan system. Moreover, the observed relationships could provide semi‐quantitative guidelines to predict the dimensions of delta–canyon–fan systems and the distribution of hydrocarbon reservoirs.